Implementatıon Of The Securıty Unıt In Performıng On Task And Role – Based On Perpol NO. 4 / 2020 In Surabaya City - Theodorus Warman; Prof Dr. Arif Darmawan, SU; Dr. Rachmawati Novaria, MM (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
One of the requirements that foreign parties consider to invest in Indonesia is the security factor. To maintain the security of the Republic of Indonesia is the duty of the Indonesian National Police. In carrying out the duties of the Indonesian National Police, assisted by Pam Swakarsa, who grew up in the community, has the task of securing areas and settlements, even now the organization's lifeline is developing, almost all require a Security Unit. Security guards have become a legitimate organization and have been recognized by the Government as a limited security personnel profession in carrying out their duties and roles as assistants to the function of the Police, as non-justice physical security to direct, prevent, crack down, and catch criminal acts that are caught in the sector of duty. The purpose of this study is to identify and analyze the implementation of the duties and roles of the Security Guard and identify and analyze the factors that hinder the Security Guard in the implementation of duties and roles in accordance with Perpolri No. 4 of 2020. The method that the author uses is a qualitative descriptive method. The data found in the field still has factors that need to be addressed, namely the direct implementation in the field starting from recruitment, training, and coaching security guards. The conclusion of this article contains how to carry out the duties and roles of security guards in accordance with Perpolri No. 4 of 2020 in the city of Surabaya.